Genetics of human infertility - Vogt, Peter H. (Monographs in human genetics, 2017)
Infertility affects more than one in ten couples worldwide and is related to highly heterogeneous pathologies sometimes only discernible in the germ line. Its complex etiology often, but not always, includes genetic factors besides anatomical defects, immunological interference, and environmental aspects. Nearly 30% of infertility cases are probabl
Gesehen am 29.07.2019
A broad treatise on the complex genetic causes of human infertility
Keywords: Molekulargenetik; Genmutation; Sterilität